A narrative review of biopsychosocial factors which impact overweight and obesity for individuals with acquired brain injury. (29th July 2021) - Driver, Simon; Douglas, Megan; Reynolds, Megan; McShan, Evan; Swank, Chad; Dubiel, Randi
ABSTRACT: Primary Objective: To discuss the biopsychosocial factors that affect being overweight or obese after acquired brain injury (ABI) Research Design: Narrative review Methods and Procedures: Based on the biopsychosocial model, we discuss the unique injury-specific factors that can affect bring overweight or obese among individuals with ABI including: (1) biological, (2) psychological and (3) social/ecological factors. Main Outcomes and Results: Injury-specific factors that impact being overweight or obese following ABI include endocrine dysfunction, pain, bowel and bladder incontinence, balance problems and motor impairment, medications, sleep quality and fatigue, alcohol and tobacco use, psychological disorders and symptoms, cognitive changes, social support, isolation, participation, transportation, independence, and knowledge. These factors may also compound general factors impacting weight management, making it difficult for individuals with ABI to maintain a healthy lifestyle. Conclusions: It is important to recognize the biopsychosocial factors that impact weight-loss and lifestyle change after ABI so that interventions can be tailored to meet individuals' unique needs. Empirical research is needed to better understand how biopsychosocial factors interact and impact overweight/ obesity after ABI.